Determination of Growth Rate Change and Accumulation Efficiency of Lemna minor Exposed to Cadmium and Lead Ions - Uysal, Y.; Taner, F. (Asian Journal of Chemistry, 2011)
The purpose of this study is to investigate the effects of lead and cadmium ions, which are present together in the same aquatic medium, on the growth of an aquatic plant, Lemna minor and to determine the accumulation potential of these metals by L. minor. Results showed that Cd ions caused a slight increase in the growth rate when they were added at a rate of 0.1 mg/L to Pb containing medium, but an increase of the Cd concentration to 5 mg/L decreased the growth rate of plants by 80 % for 0.1 mg Pb/L and 82 % for 10 mg Pb/L. Lead ions caused a slight decrease in the growth rates of plants and the results showed that observed toxic effects in plants resulted from Cd ions. Lead concentration in plants showed an increase in both metal ions containing medium in comparison to results obtained in only Pb containing medium. However, Cd accumulation of plants was not significantly affected by the presence of Pb in the medium. The concentrations of these metals in plant biomass were higher than both the mediums containing Pb and Cd ions alone.